The Effectiveness of Group Counseling in Enhancing the Psychological Well-Being of Senior High School Students - Sok, Vanna; Dara, Ravi; Kumar, Rohan (Yayasan Adra Karima Hubbi, 2025)
Psychological well-being of senior high school students is a crucial factor that influences their academic success, social relationships, and ability to adapt to various developmental pressures. However, the increasing academic workload, social dynamics, and environmental demands have placed many students in a psychologically vulnerable state, necessitating effective and sustainable intervention services. This study aims to analyze the effectiveness of group counseling in enhancing the psychological well-being of senior high school students using a mixed-methods approach that combines quantitative and qualitative data complementarily. Qualitatively, in-depth interviews and student reflection sheets were utilized to explore emotional experiences, group dynamics, and students’ perceptions of the benefits of group counseling. The quantitative results revealed significant improvements in self-acceptance, positive relationships with others, and environmental mastery. The qualitative findings corroborated these results, showing that group counseling provided a sense of safety, enhanced openness, strengthened social support, and helped students develop more constructive strategies for managing academic stress. The study concludes that the group counseling approach can be implemented as a relevant, adaptive, and sustainable guidance and counseling service to support adolescent mental health.